Relationship of Family Support to Motivate or Heal of Pulmonary Tuberculosis Patients - Hutahaean, Serri; Karim, Abdul; Nababan, Dosmaida (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2020)
Tuberculosis is an infectious disease that mainly attacks the parenchyma, tuberculosis can also be transmittedto other parts. Including meningens, kidney, bone and lymph nodes. Until now, there has not been a singlecountry that is free of Tuberculosis. The mortality and morbidity due to Tuberculosis germs in the world arealso high. In 2009, in the world, there were 1.7 million people who died of Tuberculosis (600,000 of themwomen) while there were 9.4 million new cases of Tuberculosis (3.3 million of them women). One-third ofthe world's population is infected with Tuberculosis, where most Tuberculosis sufferers are of productive age(15-55 years). To reduce the number of pulmonary Tuberculosis events, there needs to be high motivationfrom the patients themselves and the need for support from family and the surrounding environment. Thepurpose of this study was to identify the effect of family support on motivation to recover in patients withpulmonary Tuberculosis in the Kronjo District Health Center, Tangerang-BantenRegency. This research method was a quantitative study using a descriptive analytic design with a crosssectional approach, which is a study that methods to study the dynamics of the correlation betweenindependent variables and dependent variables. The sample in this study was Tuberculosis patients who wereon outpatient treatment for the past four months at the Puskesmas District of Kronjo, Tangerang-BantenRegency as many as 55 people.